2017
DOI: 10.5858/arpa.2016-0547-ra
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Technical, Bioinformatic, and Variant Assessment Approaches in the Validation of a Targeted Next-Generation Sequencing Panel for Myeloid Malignancies

Abstract: Context.-Detection of variants in hematologic malignancies is increasingly important because of a growing number of variants impacting diagnosis, prognosis, and treatment response, and as potential therapeutic targets. The use of next-generation sequencing technologies to detect variants in hematologic malignancies in a clinical diagnostic laboratory setting allows for efficient identification of routinely tested markers in multiple genes simultaneously, as well as the identification of novel and rare variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…All panels showed mean coverage over 1000x. However, we observed that TSMP did not cover CEBPA gene as homogeneously as the other panels; this might be because TSMP is an amplicon-based panel, and CEBPA is a one-exon gene lying within a CpG Island [20]. Therefore, PCR-based library preparation struggles to amplify (and capture) this gene, challenging the detection of variants in CEBPA gene (S3 Fig i.…”
Section: Comparison Of the Ngs Panels Coveragementioning
confidence: 94%
See 1 more Smart Citation
“…All panels showed mean coverage over 1000x. However, we observed that TSMP did not cover CEBPA gene as homogeneously as the other panels; this might be because TSMP is an amplicon-based panel, and CEBPA is a one-exon gene lying within a CpG Island [20]. Therefore, PCR-based library preparation struggles to amplify (and capture) this gene, challenging the detection of variants in CEBPA gene (S3 Fig i.…”
Section: Comparison Of the Ngs Panels Coveragementioning
confidence: 94%
“…FLT3 exons 14 and 15 were assessed by PCR and capillary electrophoresis using 5ng of genomic DNA per samples to detect the presence of internal tandem duplications (ITD) [19]. The ratio of FLT3-ITD to wild-type FLT3 was quantified by the Applied Biosystems sequencing software GeneScan 1 as described previously [20]. FLT3 exon 20 was tested by PCR and RFLP analysis for presence of mutations in codons p.Asp835/p.Ile836 [21].…”
Section: Genetic Molecular Testingmentioning
confidence: 99%
“…We observed TAD2 polymorphism VAFs ranging from 11.0% to 35.1% by CEBNX. This finding appears to be incongruous with the expected VAF of 50%, given the heterozygous status of this widely known polymorphism 16. We believe that this is due to the presence of fragmented libraries that therefore pose challenges for accurate VAF determination of duplication variants.…”
Section: Discussionmentioning
confidence: 86%
“…This radiation‐monitoring approach may allow, in the case of high dose‐rate radiation, for fine tuning of the doses and of the sequences of radiation pulses for personalized therapy, as well as for the development of cotherapies to increase treatment efficacy and to limit radiotherapy side effects …”
Section: Introductionmentioning
confidence: 99%
“…This radiation-monitoring approach may allow, in the case of high dose-rate radiation, for fine tuning of the doses and of the sequences of radiation pulses for personalized therapy, as well as for the development of cotherapies to increase treatment efficacy and to limit radiotherapy side effects. 12 Molecular imaging techniques are used to monitor functional and metabolic biomarkers for better orienting and monitoring personalized radiotherapeutic strategies. 13 Reliable biomarkers that mirror the effects of radiotherapy in terms of efficacy, side effects, and underlying mechanisms are a prerequisite.…”
Section: Introductionmentioning
confidence: 99%